Skrining Fitokimia Ekstrak Etanol Kulit Nanas (Ananas comosus (L.) Merr) - Inul Ahmanda Reiza; Laode Rijai; Febrina Mahmudah (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2019)
Pineapple (Ananas comosus (L.) Merr) is one type of fruit that is in demand by the community, both local and world. Pineapple has a waste part that is skin. Pineapple skin in Indonesia is generally just thrown away as waste, whereas pineapple skin contains chemical compounds that are known to have properties. The purpose of this study was to determine secondary metabolite compounds found in pineapple skin. This type of research is descriptive qualitative. Then the method used is phytochemical analysis. The Positive test of this method is characterized by a change in color. Pineapple skin samples were taken from Samarinda, East Kalimantan. The extract was carried out by maceration of dry samples using 96% ethanol solvent. The results of the pineapple skin extraction are then carried out phytochemical screening tests using certain reagents. Phytochemical screening tested included flavonoids, alkaloids, steroids, triterpenoids, tannins, phenolics, and saponins. Based on the results of phytochemical screening research, positive pineapple skin extracts contain flavonoids, alkaloids, tannins, and saponins, while negative results contain phenolic compounds, steroids, and triterpenoids.